2009
DOI: 10.1111/j.1365-2648.2008.04959.x
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation in older adults: an evolutionary concept analysis

Abstract: Numerous definitions are used to describe social isolation, but they lack uniformity, consistency and clarity; this impairs the further development and refinement of the concept. This concept analysis can offer additional understanding and a starting point for future research related to social isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
175
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(191 citation statements)
references
References 37 publications
1
175
2
8
Order By: Relevance
“…Several studies confirmed the importance of communication and social support for the health and well being in aged people (Bryant et al, 2001;Cannuscio, Block, & Kawachi, 2003;Dunér & Nordströ m, 2005;Kwong & Kwan, 2007;McCann Mortimer, Ward, & Winefield, 2008;Nagalingam, 2007;Nicholson, 2009). Access to social capital (resources available to individuals and groups through social connections and social relations with others) enables older women to maintain productive, independent, and fulfilling lives.…”
Section: Coping Strategies Of Iranian Elderly Women 583mentioning
confidence: 81%
“…Several studies confirmed the importance of communication and social support for the health and well being in aged people (Bryant et al, 2001;Cannuscio, Block, & Kawachi, 2003;Dunér & Nordströ m, 2005;Kwong & Kwan, 2007;McCann Mortimer, Ward, & Winefield, 2008;Nagalingam, 2007;Nicholson, 2009). Access to social capital (resources available to individuals and groups through social connections and social relations with others) enables older women to maintain productive, independent, and fulfilling lives.…”
Section: Coping Strategies Of Iranian Elderly Women 583mentioning
confidence: 81%
“…Social isolation can be defined as "a state in which the individual lacks a sense of belonging socially, lacks engagement with others, has a minimal number of social contacts and they are deficient in fulfilling and quality relationships" [11]. Simon et al [12] also suggest that intense feelings of emptiness, loneliness, abandonment, and forlornness are linked to an insufficient quality or quantity of an individual's network of social relationships.…”
Section: Background and Motivationmentioning
confidence: 98%
“…The opposite of social inclusion is social isolation, which may defined as "a state in which the individual lacks sense of belonging socially, lacks engagement with others, has a minimum of social contacts and they are deficient in fulfilling relationship" Nicholson [17]. The European Union has on the other hand, defined social inclusion, as having the opportunities and resources to participate fully in economic, social and cultural life and to enjoy a standard of well-being that is considered normal in the society in which we live [18].…”
Section: Social Inclusion and Community Participationmentioning
confidence: 99%